2023
DOI: 10.1108/joepp-02-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

Promoting meaningfulness in work for higher job satisfaction: will intent to quit make trouble for business managers?

Abstract: PurposeLimited empirical research has been conducted on the mediational influence of employees' intent to quit (IQ) and strategic human resource management (SHRM) to examine meaningfulness in work (MW) and job satisfaction (JS). Applying the psychological contract theory (PCT), this paper aims to explore the relationships among SHRM, IQ, MW, and JS; and the mediational influence of IQ on the relationship between SHRM and MW.Design/methodology/approachThis paper examines a proposed hypothesised model with a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…SHRM (Wright et al, 2001;Karami et al, 2004) aligned with the RBV (Wernerfelt, 1984) has been researched in the literature and has shown encouraging outcomes in terms of improved organisational performance, employee motivation and job satisfaction (e.g. Karami et al, 2004;Papatya and Hams ¸io glu, 2018;Haque and Khan, 2023). SHRM can help organisations build sustainable competitive advantage and enhance their organisational capabilities (Boxall, 1998).…”
Section: Conceptual Framework and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SHRM (Wright et al, 2001;Karami et al, 2004) aligned with the RBV (Wernerfelt, 1984) has been researched in the literature and has shown encouraging outcomes in terms of improved organisational performance, employee motivation and job satisfaction (e.g. Karami et al, 2004;Papatya and Hams ¸io glu, 2018;Haque and Khan, 2023). SHRM can help organisations build sustainable competitive advantage and enhance their organisational capabilities (Boxall, 1998).…”
Section: Conceptual Framework and Discussionmentioning
confidence: 99%
“…Karami et al. , 2004; Papatya and Hamşioğlu, 2018; Haque and Khan, 2023). SHRM can help organisations build sustainable competitive advantage and enhance their organisational capabilities (Boxall, 1998).…”
Section: Conceptual Framework and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of employee voice has increased in recent years, and Twitter is becoming more popular among researchers as a source of information on employee attitudes. Employees use Twitter to share their opinion regarding job-related issues (e.g., job satisfaction, engagement, or WFH) as an effective channel for employee voice [32,33]. Many scholars have suggested that Twitter has changed many aspects of employee and organisational outcomes for social studies research [9,34].…”
Section: Twitter and Employee Voicementioning
confidence: 99%